Poczucie satysfakcji z życia a gotowość rodziców do aktywnego udziału w rehabilitacji dziecka z niepełnosprawnością = Sense of life satisfaction and parents` readiness to active participation in the rehabilitation of a disabled child - Stosor, Alina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the article is the sense of life satisfaction of parents of children with disabilities in the context of their activity in the process of child rehabilitation. The concept of life satisfaction based on modern concepts of happiness is discussed. Then, the problem of functioning of the family of a disabled child was presented. In the further part of the article methodological assumptions and research results are presented. The work ends with conclusions and postulates for pedagogical practice.
Keywords: poczucie satysfakcji z życia; rodzina dzieci niepełnosprawnych; rehabilitacja; aktywność rodzicielska w terapii dziecka; sense of satisfactions with life; family of children with disabilities; rehabilitation; parentalactivity in child therapy